Observations of Heterospecific Courtship Behaviour in an Isolated Population of Ross’s Gulls (Rhodostethia rosea) - Maftei, Mark; Davis, Shanti E.; Mallory, Mark L. (ARCTIC, 2016)
Heterospecific sexual behaviour is notable because it should be strongly deterred by natural and sexual selection. Here we report observations of both male and female Ross’s Gulls (Rhodostethia rosea) routinely engaging in sexual displays directed towards other species during the breeding season at a small, remote colony in the Canadian High Arctic. We suggest that in small, reproductively isolated populations, directing stereotyped courtship displays towards heterospecific partners may allow individuals to advertise fitness and experience to both male and female conspecifics and also accelerate hormonal development and readiness to mate during the brief and unpredictable High Arctic breeding season. Le comportement sexuel hétérospécifique est remarquable, car celui-ci devrait être fortement dissuadé par la sélection naturelle et sexuelle. Ici, nous faisons mention d’observations de mouettes rosées mâles et femelles (Rhodostethia rosea) exhibant régulièrement des comportements sexuels envers d’autres espèces pendant la saison de reproduction dans une petite colonie éloignée de l’Extrême-Arctique canadien. Nous suggérons qu’au sein des petites populations reproductivement isolées, le fait d’axer la pariade stéréotypée sur des partenaires hétérospécifiques pourrait permettre aux individus de faire état de leur forme physique et de leur expérience à leurs congénères mâles et femelles, en plus d’accélérer le développement hormonal et l’état de préparation à l’accouplement pendant la brève saison imprévisible de reproduction dans l’Extrême-Arctique.